PENGEMBANGAN KOMIK FABEL SEBAGAI SUPLEMEN PENDIDIKAN LINGKUNGAN DALAM RANGKA KAMPANYE PELESTARIAN FLORA DAN FAUNA BAGI SISWA KELAS 1 MI AL – ABROR MAGETAN TAHUN 2016/2017 - Restiana Sari Nadia Alfi M, Ika septiarini, Fahriani Limas K. dan Nurul Suci Annisa, Candra Dewi, S. (Universitas Muhammadiyah Ponorogo, 2017)
In the process of introducing the environment for students not only using explanations but also by using the media. Media that can assist in environmental conservation campaigns so that the learning process of environmental education is not boring. This study aims to develop comic fable media on environmental education learning as an environmental conservation campaign based on expert judgment. The result of research of fable comic development as environmental education suplement of flora and fauna preservation can be declared very effective and feasible to be used.